1990
DOI: 10.1063/1.346881
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of annealing parameters for the growth of epitaxial Ba2YCu3O7−x films on LaAlO3(100)

Abstract: The superconducting and structural properties of Ba2YCu3O7−x (BYCO) films on LaAlO3(100) substrates can be improved by carefully optimizing the post-deposition annealing parameters. Films are grown by co-deposition of BaF2, Y, and Cu in the correct stoichiometric ratio to within 1% of 2:1:3. Annealing parameters in an ex situ furnace, including the ambient, annealing temperature, oxidation temperature, and duration of anneals are systematically studied. Films are characterized for epitaxial quality (χmin), mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…19 The BaF 2 -process conditions are described in detail elsewhere. 20,21 The typical thickness of each sol-gel layer is 100-200 nm. Figure 1 is an x-ray diffraction -2 scan from Cu K␣ radiation for a YBCO/STO/Ni͑100͒ sample ͑100 nm thick YBCO on 500 nm Nb:STO͒.…”
mentioning
confidence: 99%
“…19 The BaF 2 -process conditions are described in detail elsewhere. 20,21 The typical thickness of each sol-gel layer is 100-200 nm. Figure 1 is an x-ray diffraction -2 scan from Cu K␣ radiation for a YBCO/STO/Ni͑100͒ sample ͑100 nm thick YBCO on 500 nm Nb:STO͒.…”
mentioning
confidence: 99%
“…5,25,26 Moreover, the ex-situ annealing in oxygen atmosphere has been widely employed to optimize the crystallinity and eliminate oxygen deficiency for complex oxide films. 21,27,28 But it was also shown that the high temperature annealing may also facilitate the strain relaxation in large lattice-mismatched systems. 17,29 Therefore, the effect of ex-situ annealing on substrate coherency should be multiplicate, and surely needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This is clear from our results presented above and the results of several other groups. [1][2][3][4][5][6][7][27][28][29] McIntyre et al have reported on the J c dependence of film thickness for similar post annealed films. 27 They showed that there is a correlation between the density of 1-2-4 stacking faults and J c in that the 1-2-4 stacking faults act as planar core type flux pinning centers thereby increasing J c .…”
Section: Discussionmentioning
confidence: 99%
“…The BaF 2 coevaporation technique has proven superior in combination with optimized ex situ post annealing at low oxygen partial pressures. [1][2][3][4][5][6][7] In general, films processed under these conditions have a good surface morphology with no large surface outgrowths, high transition temperatures (T c ), high values of the critical current density (J c ) and good microwave properties. [3][4][5][6][7] These good properties can be obtained only if the YBCO thin films are grown on special substrates.…”
Section: Introductionmentioning
confidence: 99%